Association between Severe Dehydration in Rotavirus Diarrhea and Exclusive Breastfeeding among Infants at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Dwi Prasetyo; Iesje Martiza Sabaroedin; Yudith Setiati Ermaya; Yati Soenarto (Journal of Tropical Medicine)
Background. Rotavirus is the leading cause of severe acute diarrhea in children. Infants who are exclusively breastfed develop fewer infections and have less severe illnesses. This study aimed to determine association between severe dehydration in rotavirus diarrhea and exclusive breastfeeding. Methods. This is a cross-sectional study in infants ≤ 6 months old with acute diarrhea in Dr. Hasan Sadikin Hospital, Bandung, Indonesia. Results. From 134 infants ≤ 6 months old with acute diarrhea enrolled from April 2009 to December 2012, there were 88 (65.6%) boys and 46 (34.4%) girls in this study. Rotavirus was detected in 60 (44.8 %), 32 (53.3%) of whom were exclusively breastfed. From rotavirus positive subjects, severe dehydration occurred in 4 (12.6%) exclusively breastfed infants and 6 (21.5%) not exclusively breastfed infants. No significant association was found between severe dehydration and exclusive breastfeeding (p = 0.491) in rotavirus diarrhea. Conclusions. In rotavirus diarrhea, there was no significant association between exclusive breastfeeding and severe dehydration.